2019
DOI: 10.1016/j.seizure.2018.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver impact and health service use in high and low severity Dravet syndrome: A multinational cohort study

Abstract: A R T I C L E I N F O Keywords:Dravet syndrome Health service use Rare disease Developmental encephalopathy Caregiver burden A B S T R A C TPurpose: To estimate costs associated with the current management of Dravet syndrome (DS), explore psychosocial aspects of the disease in caregivers and siblings, and identify patient characteristics associated with higher costs in a large, predominantly European survey cohort of patients and their caregivers conducted in 2016. Methods: Health and social care resource use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(86 citation statements)
references
References 25 publications
5
77
0
4
Order By: Relevance
“…This analysis revealed that DS patients had the greatest use of ancillary treatments while physiotherapist visits accounted for the highest proportion of visits to all ancillary specialists across the three groups. This aligns with the DISCUSS survey, which reported that physiotherapy accounted for the highest non–seizure‐related mean cost per patient in Germany …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This analysis revealed that DS patients had the greatest use of ancillary treatments while physiotherapist visits accounted for the highest proportion of visits to all ancillary specialists across the three groups. This aligns with the DISCUSS survey, which reported that physiotherapy accounted for the highest non–seizure‐related mean cost per patient in Germany …”
Section: Discussionsupporting
confidence: 86%
“…Although more patients in the DS cohort experienced seizures at a shorter frequency, whether and to what extent this accounts for the higher socioeconomic impact of the disease is beyond the scope of this comparative analysis (matching of patients by seizure frequency would not be possible because of the small sample sizes). Nevertheless, a recent study conducted by Lagae et al on a large cohort of 584 DS patients showed that excluding medication, non–seizure‐related costs dominated costs of care, suggesting that the higher costs incurred by patients with DS compared with DRE in this study could be explained in part by the higher burden of their additional symptoms …”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations